The endocytic protein alpha-adaptin is required for Numb-mediated asymmetric cell division in Drosophila. - Berdnik, D.; Torok, T.; Gonzalez-Gaitan, M.; Knoblich, J.A. (Developmental Cell, 2002)
During asymmetric cell division in Drosophila sensory organ precursor cells, the Numb protein localizes asymmetrically and segregates into one daughter cell, where it influences cell fate by repressing signal transduction via the Notch receptor. We show here that Numb acts by polarizing the distribution of alpha-Adaptin, a protein involved in receptor-mediated endocytosis. alpha-Adaptin binds to Numb and localizes asymmetrically in a Numb-dependent fashion. Mutant forms of alpha-Adaptin that no longer bind to Numb fail to localize asymmetrically and cause numb-like defects in asymmetric cell division. Our results suggest a model in which Numb influences cell fate by downregulating Notch through polarized receptor-mediated endocytosis, since Numb also binds to the intracellular domain of Notch.